2022
DOI: 10.1136/openhrt-2022-002160
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of approaches to determine echocardiographic outcomes for children with latent rheumatic heart disease

Abstract: BackgroundScreening programmes using echocardiography offer opportunity for intervention through identification and treatment of early (latent) rheumatic heart disease (RHD). We aimed to compare two methods for classifying progression or regression of latent RHD: serial review method and blinded, side-by-side review.MethodsA four-member expert panel reviewed 799 enrolment (in 2018) and completion (in 2020) echocardiograms from the GOAL Trial of latent RHD in Uganda to make consensus determination of normal, bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In a study of 55 Aboriginal Australians, a 23% rate of progression to definitive RHD was detected during a follow-up period of 2.5 to 5.0 years. 25 In a study conducted in Uganda, improvement of RHD was seen in 18 of 43 patients, and only 4 of the 43 patients developed definitive RHD over the 2-year follow-up period. 26 These studies concluded that the disease progression was mostly due to morphological changes in the mitral valve and less commonly due to aortic valve involvement.…”
Section: Introductionmentioning
confidence: 97%
“…In a study of 55 Aboriginal Australians, a 23% rate of progression to definitive RHD was detected during a follow-up period of 2.5 to 5.0 years. 25 In a study conducted in Uganda, improvement of RHD was seen in 18 of 43 patients, and only 4 of the 43 patients developed definitive RHD over the 2-year follow-up period. 26 These studies concluded that the disease progression was mostly due to morphological changes in the mitral valve and less commonly due to aortic valve involvement.…”
Section: Introductionmentioning
confidence: 97%
“…The WHF criteria are complex and resource intensive, requiring skilled echocardiographers and costly equipment. There are also concerns regarding reproducibility and the propensity of these criteria to misclassify normal cases as ‘borderline RHD’ 2–9…”
Section: Introductionmentioning
confidence: 99%